Pro Internet Explorer 8 & 9 Development Developing Powerful Applications for The Next Generation of IE - Crowley, Matthew (Apress : Imprint: Apress, 2010)
This book is an in-depth guide to writing applications that embrace and extend the new features and capabilities of Windows Internet Explorer 8 and 9. With solid instruction, hands-on examples, and expert insight direct from the source into extending the browser, you'll learn how to create and maintain powerful applications for Microsoft's next-generation Internet platform. Join author Matthew Crowley as you discover how to take advantage of new features like accelerators, WebSlices, and search providers, and create intense web experiences for the browser that ships by default with the popular Windows 7 operating system. If you're interested in creating and shipping high-quality, feature-rich applications for the Web, Pro Internet Explorer 8 & 9 Development is the only resource you need.